The Effect of Trehalose on Dispersion of Ice Crystals and Consistency of Low-Fat Ice Cream - Landikhovskaya Anna V.; Tvorogova Antonina A.; Kazakova Natalia V.; Gursky Igor A. (Техника и технология пищевых производств)
Introduction. The research objective was to establish the effect of the complete and partial replacement of sucrose by trehalose on the dispersion of ice crystals in ice cream with a low mass fraction of fat and solids. Study objects and methods. The present research featured three test samples of ice cream with a 3% mass fraction of fat: one with a complete replacement of sucrose (15.5%) and two with a partial replacement of 7.5% and 3%. In the control sample, the mass fraction of sucrose was 15.5%. To control the dynamic viscosity indicator of consistency, the research employed such an advanced method as rotational viscometry. Microstructure methods were used to determine the dispersion of ice crystals and the air phase. Results and discussion. The usage of trehalose in the production of low-fat ice cream in the amounts of 3.0%, 7.5%, and 15% increased the dispersion of ice crystals and preserved it during storage. After three months of storage, most ice crystals in the test ice cream samples had a size of ≤ 45 μm with an organoleptic sensibility of ≤ 50 μm, while in the control sample (15.5% of sucrose) it did not exceed 60 μm. The experiment determined the effect of trehalose on the consistency of ice cream according to the following indicators: dynamic viscosity, overrun, and dispersion of the air phase. 15.5% of trehalose increased the dynamic viscosity of ice cream mix by 1.2 times as compared to the sample with the same concentration of sucrose. According to the average diameter of air bubbles, trehalose helped to preserve the dispersion of the air phase during storage. After three months, Sample 1 with 15.5% of trehalose demonstrated the maximum dispersion, which was 17% higher than in the control sample with a sucrose mass fraction of 15.5%. Conclusion. The complete (15.5%) and partial (3% and 7.5%) sucrose replacement by trehalose in low-fat ice cream increased the dispersion of ice crystals and improved its consistency. Unlike the sample with 15.5% of sucrose, samples with trehalose had smaller ice crystals, which remained the same after three months. The trehalose samples had a better dynamic viscosity and air saturation. The research requires a further study of dispersion of ice crystals after 12 months of storage.